In vivo micronucleus test as a biomarker of genotoxicity in free-range goats from suspected contaminated environment - Jubril, Afusat Jagun; Omadevuaye, Theodora Omamuyovwi; Adekola, Adewole Augustine (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Environmental pollution and the resultant genotoxicity, has become a major livestock, public and environmental health concern with direct impact on the ecosystem. Here, application of micronucleus test and frequency score as a potential biomarker of genotoxic effect and bio-monitoring have been discussed aiming at exploring environmental polution. Materials and methods: A total of 100 domestic goats slaughtered at the Bodija Municipal Abattoir were used in this study. Blood sample was analyzed for the quantification of the hematological parameters. The bone marrow smear was viewed microscopically for the detection of micronucleus and other nuclear abnormalities. The frequency of micronucleus was quantified to group the sampled goats into MN-positive and MN-negative groups for further analysis. Results: MN was positive in 21% of the sampled goats with varying frequency ranging from (6-15% count per 2000 cells examined). Bi-nucleation, multi-nucleation and high mitotic index were also observed and quantified. The packed cell volume, mean corpuscular volume and neutrophil count were significantly lower (P<0.05) in the MN-positive groups while anemia was reported in 33.3% of the MN-positive goats. Conclusion: The finding indicates the prevalence and frequency of micronucleus as a biomarker of genotoxicity and an indicator of exposure to environmental genotoxic subtances. Hence, this highlights the relevance of these goats as important sentinel animal model. These findings, therefore, serve as a preliminary data for further studies on the latent genotoxic environmental contaminants and their potential deleterious impact. http://doi.org/10.5455/javar.2017.d225